Padi2U: mobile application development for paddy management in KADA Kelantan - Roslin, Nor Athirah; Che'ya, Nik Norasma; Ismail, Mohd Razi; Md Azali, Fadzilah; Abd Gani, Siti Salwa (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Mobile application in agriculture has a bright future to deliver information to users about crops and the right method of crop management for high yield production. Nowadays, almost all people own a smartphone and with help of this technology the demand for mobile application is higher. Therefore, a mobile application known as Padi2U created to provide information about a new variety of paddy (PadiU Putra) and its potential to help farmer increase the yield production with minimal cost of management. In this application, the user is able to view multispectral images captured by Unmanned Aerial Vehicle (UAV) for one season of paddy development located at Kampung Lundang Paku, Kelantan. User will able to identify the paddy growth stage, soil condition and water level in each plot at the paddy field. From this mobile application, users learn about paddy and method to improve current management for efficient work process and increase the yield.